2017
DOI: 10.4172/pharmaceutical-sciences.1000246
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Antioxidant and Cytotoxic Effects of Methanol Extracts of Vitex negundo, Lantana camara, Bauhinia variegata and Barringtonia racemosa on Human Cancer Cell lines

Abstract: In current study, the phytochemical, antioxidant and cytotoxic effects of methanol extracts of Vitex negundo, Lantana camara, Bauhinia variegata and Bauhinia racemosa were reported. Methanol extract of medicinal plants (V. negundo, L. camara, B. variegata and B. racemosa) were extracted using different extraction methods and then tested for their antioxidant activity by 2,2-diphenylpicrylhydrazyl, superoxide scavenging method, chelation of metal ions and cytotoxic potency using MTT assay on human cancer cell l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
2
7
0
Order By: Relevance
“…Linn, the highest total phenolic and Bauhinia variegata flavonoid content was observed in methanol extracts whereas water extract had lowest amount of phenolics. As per the study by Badgujar et al, (2017), the phenolic and flavonoid content in the methanol extracts of leaves were 112.0 ± 2.43 mg GAE/g and 20.73 ± 1.43 mg QE/g dry extract. In the same study, the IC 50 value of methanol extract for DPPH radical scavenging activity was reported to be 117±3.33µg/ml (Badgujar et al, 2017).…”
Section: Forsupporting
confidence: 56%
See 1 more Smart Citation
“…Linn, the highest total phenolic and Bauhinia variegata flavonoid content was observed in methanol extracts whereas water extract had lowest amount of phenolics. As per the study by Badgujar et al, (2017), the phenolic and flavonoid content in the methanol extracts of leaves were 112.0 ± 2.43 mg GAE/g and 20.73 ± 1.43 mg QE/g dry extract. In the same study, the IC 50 value of methanol extract for DPPH radical scavenging activity was reported to be 117±3.33µg/ml (Badgujar et al, 2017).…”
Section: Forsupporting
confidence: 56%
“…As per the study by Badgujar et al, (2017), the phenolic and flavonoid content in the methanol extracts of leaves were 112.0 ± 2.43 mg GAE/g and 20.73 ± 1.43 mg QE/g dry extract. In the same study, the IC 50 value of methanol extract for DPPH radical scavenging activity was reported to be 117±3.33µg/ml (Badgujar et al, 2017). This is in agreement with our study where methanol extracts were found to possess high amount of phenolics and flavonoids as well as free radical scavenging property in comparison to extracts prepared using other solvents.…”
Section: Forsupporting
confidence: 56%
“…Maceration [32] Leaves -Methanol -Phenols (constituents not stated) -Flavonoids (constituents not stated) Percolation [42] Leaves -Ethanol -Flavonoids (constituents not stated)…”
Section: Summary Of Methods For Extraction Of Vitex Negundo Linn and Phytochemicals Extractedmentioning
confidence: 99%
“…extracted negundoside utilizing the solvent ethanol from the leaves of the sample. In the study "In vitro Antioxidant and Cytotoxic Effects of Methanol Extracts of Vitex negundo, Lantana camara, Bauhinia variegata and Bauhinia racemosa on Human Cancer Cell lines" by Badguhar et al [32] , V. negundo Linn leave extracts from cold maceration were phenols and flavonoids utilizing the solvent methanol.…”
Section: In the Study Conducted By Abidin Et Al (2014) Entitledmentioning
confidence: 99%
“…In India liver, lungs, breast, rectum, colon and stomach cancers are frequently detected. [10] Fig. 1.0 -Bauhinia racemosa (Lam.…”
Section: Introductionmentioning
confidence: 99%